Dielectric and gas sensing properties of in situ electrochemically polymerized PPy-MgO-WO3 nanocomposite films - Abbas, Yahya; Hasan, Ahmad A. (Iraqi Journal of Science, 2021)
A polypyrrole-based ammonia-detection gas sensor was studied in this work. Under a 1.6 V electrodeposition potential, polypyrrole (PPy) was electrochemically synthesized from an aqueous solution of 0.1 M pyrrole and 0.1 M oxalic acid. An extension to the polypyrrole films was applied through electrochemical deposition on indium tin oxide (ITO), using the metal oxide nanoparticles of MgO and WO3. These films were investigated for their sensing behavior towards NH3 at different working temperatures and different weight percentages of nanoparticles .The measurements of A.C conductivity were conducted over a frequency range of 101-105 Hz and temperature range of 298-423 K . The highest electrical conductivity was equal to 3.67x10-1 Ω.cm-1 at a temperature of 323 K and frequency of 105H z. The experimental results showed that the sensitivity of the undoped and doped PPy with nanoparticle films to ammonia gas changes with the change in temperature and weight percentage.